Legal argumentation and constitutional principles: their impact on private law (2014)
This paper is intended to show how the phenomenon of constitutionalization has sheltered all that has been possible, reflecting not only its ability to influence the way we understand the law, but also covered the orbit of the strictly private, referring exactly to the exercise of autonomy and within that, specifically formation, holding, execution and settlement of contracts. It starts defining the concepts of legal argumentation and neoconstitutionalism then indicates how to establish a necessary connection between them and mentions the different degrees of constitutionalization of law. It is regarded as the neo- constitucionalization and legal arguments, in the case of Colombia, have generated a state of judicial activism, which was intended to cover all possible fields in the practice of law including the law of contracts. Thus it is impossible to look at all this and not relate to the failure of judicial activism in other places and how this failure could be repeated in Colombia and how it has created a false expectation of such activism in the legal field in Colombia.